Removal of Tannic Acid Stabilizes CuO Nanoparticles from Aqueous Media by PAFC: Effect of Process Conditions and Water Chemistry - Rizwan Khan; Muhammad Ali Inam; Kang Hoon Lee (Molecules, 2021)
The increased utilization of CuO nanoparticles (CuO NPs) in various fields has raised concerns about their discharge into water containing a wide range of organic ligands. Moreover, the adsorption of these ligands can stabilize the CuO NPs in drinking water treatment plants. Thus, their removal from potable water is important to mitigate the risk to humans. The present study explored the efficacy of the coagulation–sedimentation (C/S) process for the removal of tannic acid (TA)-stabilized CuO NPs using polyaluminum ferric chloride (PAFC) as a coagulant. Moreover, the influence of process conditions (stirring speed) and water chemistry (i.e., pH and ionic strength (IS)) were also investigated to determine their impact on removal. The results showed that stirring speed in the reaction phase significantly affected the removal due to increased flocculation compared with stirring speed in the mixing phase. In addition, pH and IS affect the colloidal stability and removal efficiency of CuO NPs. A relatively better removal performance (<99%) of CuO NPs was found at lower coagulant dosage in the pH range 6–8. The addition of organic ligands reversed the surface charge potential and enhanced the colloidal stability of CuO NPs, resulting in the destabilization of TA-CuO NPs, thereby reducing the optimum PAFC dosage for removal. By contrast, the IS above the critical coagulation concentration decreased the removal efficiency due to inhibition of the ionic activity of PAFC hydrolysate in the aqueous environment. Fourier transform infrared findings of TA-CuO NPs composite flocs suggest that the primary removal mechanism might be mediated via the combined effect of neutralization, complexation as well as adsorption.